A new method for evaluating the retentive efficacy of different denture adhesives - Simone Gomes Dias de Oliveira; Carlos Enrique Cuevas-Suárez; Carine Tais Welter Meereis; Josiane Kuhn Rutz; Ricardo Alfredo Carrillo-Cotto; Cesar Henrique Zanchi; Rafael Guerra Lund; Evandro Piva (Universidade Estadual de Campinas, 2018)
Aim: The aim of this study was to evaluate a new method for measuring the retention values of different denture adhesives. Methods: The adhesive strength values of three different commercial denture adhesives (Corega powder, Corega adhesive tape and Ultra Corega cream) were evaluated using three different moisturizing agents (distilled water, artificial saliva and natural saliva). The adhesive test was performed on a universal testing machine, after applying the adhesive products to acrylic resin specimens, under two different test conditions (wetting or dipping). Tensile bond strength values in MPa were obtained for each denture adhesive presentation and test condition. Viscosity of the denture adhesives mixed with the different moisturizing agents was determined using a rotary rheometer. Maximum viscosity values were analyzed using the one-way ANOVA test. Tensile bond strength data was analyzed using Kruskal-Wallis and the Tukey's test. Pooled data of each denture adhesive presentations for all test conditions was also carried out. Correlation between viscosity and pooled tensile strength values was analyzed through linear regression analysis. A significance level of α=0.05 was set for all analyses. Results: Results showed that statistically higher adhesion strength was obtained with tape and cream adhesives when using natural saliva as moisturizing agents (p<0.05). The adhesive strength values obtained with the dipping method were similar to those obtained with the conventional wetting method. The denture retention strength was influenced by both the denture adhesive type and moisturizing agent used. Conclusion: The dipping method showed to be a reliable test capable to simulate the oral conditions and should be better explored in further studies.